L’Atlas der Fotos, Collagen und Skizzen di Gerhard Richter: un esempio di mnemotecnica frammentaria (Materiali di Estetica. Terza serie, 2020)
The present paper analyzes Gerhard Richter's Atlas der Fotos, Collagen und Skizzen, which is not just a repository of images from where the German artist extracts the subjects for his paintings, but also has autonomy on its own. Even though it might be considered as an anomic archive and it includes images that are mostly ordinary, this impressive work of archive serves a mnemonic task since it draws together the artist's personal experience and the collective conscience and memory of the past. It is shown that, through the montage, the artist brings up some images that act as punctum and break the studium that seems to run the Atlas; in this manner he creates the conditions for the postwar Germany traumatic memory to emerge from its latent stage. Secondly, the present text focuses on the comparison with Aby Warburg's Mnemosyne Atlas, which may be considered an antecedent of Richter's Atlas.
Keywords: Gerhard Richter; Atlas; Archive; Memory; Aby Warburg